2018
DOI: 10.1007/s00439-018-1908-x
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping and fine-mapping of birth weight loci in the Black Women’s Health Study

Abstract: Several genome-wide association studies (GWAS) have identified genetic variants associated with birth weight. To date, however, most GWAS of birth weight have focused primarily on European ancestry samples even though prevalence of low birth weight is higher among African-Americans. We conducted admixture mapping using 2918 ancestral informative markers in 2596 participants of the Black Women's Health Study, with the goal of identifying novel genomic regions where local African ancestry is associated with birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Results from the Black Women's Health Study show evidence of a shared genetic ancestry component between low birth weight and T2D [15,44]. Genome-wide admixture mapping of both traits found that excess local African ancestry in chromosome 12q14 was associated both with lower birth weight and higher T2D risk (Fig.…”
Section: Shared Genetic Component Between Low Birth Weight and Type 2...mentioning
confidence: 97%
See 2 more Smart Citations
“…Results from the Black Women's Health Study show evidence of a shared genetic ancestry component between low birth weight and T2D [15,44]. Genome-wide admixture mapping of both traits found that excess local African ancestry in chromosome 12q14 was associated both with lower birth weight and higher T2D risk (Fig.…”
Section: Shared Genetic Component Between Low Birth Weight and Type 2...mentioning
confidence: 97%
“…Excess local African ancestry in chromosome 12q14 is associated with T2D risk and low birth weight in African Americans. Admixture mapping results from the Black Women's Health Study (BWHS) [15,44] has shown a shared genetic ancestry component between low birth weight and T2D in the adult file. The BWHS found an inverse association between excess local African ancestry at 12q14 and birth weight (Z ¼ À4.7; P ¼ 2.4 Â 10 À6 ).…”
Section: Shared Genetic Component Between Low Birth Weight and Type 2...mentioning
confidence: 99%
See 1 more Smart Citation
“…In smaller cohorts that are underpowered for discovering individual loci, gene-based associations can sometimes be useful in conjunction with functional follow up [64]. Studies of traits with elevated prevalence in African Americans, such as BMI, prostate cancer, and low birth weight [65-67] have analyzed genome-wide significant loci by local ancestry or more easily fine-mapped variants with narrower LD.…”
Section: Successful Gwas Strategies In African and African Descent Pomentioning
confidence: 99%